2015
DOI: 10.1039/c5ta06840a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical architecture of WS2nanosheets on graphene frameworks with enhanced electrochemical properties for lithium storage and hydrogen evolution

Abstract: Three-dimensional interlayer-expanded WS2/3DG architecture exhibits enhanced electrochemical properties for lithium storage and hydrogen evolution due to synergistic effects between the components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 65 publications
2
91
0
Order By: Relevance
“…[90] Post annealing treatment can evaporate volatile species intercalated in the hydrothermal/ solvothermal MX 2 nanosheets and decrease the expanded interlayer spacing by restacking. [82,84,85,[91][92][93] …”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[90] Post annealing treatment can evaporate volatile species intercalated in the hydrothermal/ solvothermal MX 2 nanosheets and decrease the expanded interlayer spacing by restacking. [82,84,85,[91][92][93] …”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…It exhibits a high capacity of 766 mA h g −1 at a current density of 100 mA g −1 after 100 cycles delivering nearly 98% capacity retention, while the annealed composite electrode shows continuous and progressive capacity fading and yields a capacity of only 416 mA h g −1 after 100 cycles. [91] …”
Section: Application In Lithium Ion Batteries (Libs)mentioning
confidence: 99%
“…The produced compounds such as intermediate ternary Na x MoO y and Na x WO y [54][55][56] crystalline phase could form and condense on the substrates for subsequent sulfurization. At the beginning, these Na-containing particles which were similar to PTAS and PTCDA [57] seeds could provide nucleation sites on the substrate [58,59] and then were sulfurized into the oxi-chalcogenide nanoparticles encased in a fullerene like shell [53,60].…”
Section: Growth Of MXmentioning
confidence: 99%
“…Besides MoS 2 , first time 3D mesoporous MoSe 2 /rGO foam was synthesized by hydrothermal method, which was used as anode in LIB [78]. Additionally, L-TMD NSs such as the SnS 2 and WS 2 have also been combined with the 3D porous structure to improve their electrochemical performance [80][81][82][83][84]. Recently, a facile two-step route to synthesize 3D interconnected graphene frameworks embedded with homogeneously distributed SnS 2 nanoplates (SSG) by using GO NSs, SnCl 4 .5H 2 O and L-cys as source materials has reported.…”
Section: D Porous Structures With 2d Graphene/porous Cnfmentioning
confidence: 99%
“…Firstly SnO 2 NPs decorated on GO NSs via water bath strategy [85] and then directly transformed into SnS 2 by hydrothermal treatment with L-cys as reducing agent and sulfur source [81]. Additionally, Huang et al [82] reported a layered composite WS 2 with 3D-graphene interconnected networks by hydrothermal method at relatively low temperature for LIB and hydrogen evolution reactions.…”
Section: D Porous Structures With 2d Graphene/porous Cnfmentioning
confidence: 99%